The Role of Intelligence Unit in Carrying Out Early Detection of Violent Theft Cases in Cimahi City - Wahjudin, Lisdawati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Factors that influence in tackling the crime of theft with violence there is a support factor with the existence of cooperation with the community, motorized community organizations and convicts who can make it easier to find information and monitor the network perpetrators theft with robbery violence, the location and the perpetrators who come from It is very difficult from various circles, therefore cooperation from various groups is very much needed in early prevention and suppressing the theft with violence. This study targeting  find out how the role of intelegence carrying out early detection of cases of violent theft in  jurisdiction  Cimahi police, cases of violent theft  violate law and disrupt public security so that the role of intelligence is needed to investigate, security and fundraising. This study uses a descriptive method, which describes the data according to the case, this research was conducted by interview, literature study and documentation. Based on the results of the research and discussion, it can be concluded that in dealing with cases of violent theft carried out Cimahi police intelligence unit with early detection, monitoring, socializing in order to obtain information to be presented to the leadership so that can then take a policy and can coordinate with other relevant parties who are authorized to tackle the crime of theft with violence in the jurisdiction Cimahi Police.